Factors affecting dry matter intake, daily milk yield and feed conversion ratio in crossbred cows - B. N. SAIKIA, T. BORPUZARI; R. N. GOSWAMI, JAKIR HUSSAIN, R. ROYCHOUDHURY T. K. AMONGE, D. C. MILI, A. AZIZ (Indian Journal of Animal Production and Management, 2020)
The experiment was carried out with 10 Jersey crossbred and 10 Holstein-Friesian crossbred cows during four seasons viz. Pre-monsoon, Monsoon, Post-monsoon and Winter in 2016-17. The objectives was to study the effect of feeding practice, genetic group and season on the dry matter intake (DMI), daily milk yield (DMY) and feed conversion ratio (FCR) in crossbred cows. The overall mean DMI, DMY and FCR was 3.48±0.04 percent, 8.44±0.08 kg and 1.44±0.02, respectively. The effect of feeding practice and genetic group was highly significant (P<0.01) on the DMI, DMY and FCR, whereas the effect of season was highly significant (P<0.01) on DMI and DMY in crossbred cows. The mean DMI/100 kg body weight and DMY in crossbred cows were significantly higher on total mixed ration (TMR) than separate feeding, while FCR was lower on TMR than separate feeding practice. The DMI/100 kg body weight of Jersey crossbred and its FCR was significantly more than Holstein-Friesian crossbred, but the DMY was significantly lower in Jersey crossbred cows. Significantly highest DMI/100 kg body weight and DMY were observed during pre-monsoon season. The FCR during winter season was apparently lowest.